Dielectric and work function engineered TFET for ambipolar suppression and RF performance enhancement. Issue 9 (4th April 2016) - Raad, B.; Nigam, K.; Sharma, D.; Kondekar, P.
Abstract : A novel approach to suppress the ambipolar behaviour and enhance RF parameters is proposed for the first time. For this, the dielectric and gate material work function engineering is used to suppress the ambipolar behaviour individually. Further, the combination of gate dielectric and gate material work function engineering is used to suppress the ambipolar conduction in huge amount and to eliminate the hot carriers effects. Apart from these, the proposed work improves the ON‐state current and RF figures of merit for symmetric devices.